Peran Teknologi dalam Meningkatkan Efisiensi Audit Keuangan - Rasyd Yudha Harahap; Reza Hanafi Lubis (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study discusses the role of technology in improving the efficiency of financial audits in the digital era. The rapid development of information technology has transformed traditional manual audit methods into more automated, accurate, and efficient ones. This study analyzes various technologies used in modern audits, such as audit software, artificial intelligence (AI), big data analytics, blockchain, and cloud-based systems, and their impact on the efficiency of the audit process. The implementation of technology allows auditors to access and analyze data faster, improve the accuracy of audit reports, and reduce the potential for human error. In addition, technology increases data transparency and security by reducing the risk of information manipulation and leakage. However, challenges remain, such as high implementation costs, resistance from traditional auditors, and cybersecurity risks. To overcome these challenges, optimal strategies that can be implemented include improving auditor training, strengthening IT infrastructure, and implementing a hybrid approach in the audit process. The results of the study show that organizations that adopt technology in financial audits experience an increase in efficiency of up to 60% and a significant reduction in audit errors. Therefore, the integration of technology in audits needs to be carried out in a structured manner and supported by all stakeholders so that its benefits can be optimized.